2016
DOI: 10.1007/s11655-016-2736-2
|View full text |Cite
|
Sign up to set email alerts
|

Recent highlights of Chinese medicine for advanced lung cancer

Abstract: Owing to its unique superiority in improving quality of life and prolonging survival time among advanced lung cancer patients, Chinese medicine (CM) has, in recent years, received increased attentions worldwide. We utilized a bibliometric statistical method based on MEDLINE/GoPubMed to conduct a comprehensive analysis of the current application status of CM in lung cancer, by including annual and accumulated publications, origin distribution of countries and journals, and keywords with a higher frequency score… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Compared with 19DEL, L858R lung cancer patients have a weaker response to TKI treatment, a worse prognosis, and less survival benefit (mPFS: 9.0 vs. 7.0 months, mOS: 25 vs. 16 months) (41,42). Relevant studies suggest that patients with exon 21 deletion mutations benefit more when treated with TCM combined with EGFR-TKIs, and mPFS is prolonged by 5 months (14). However, the sample size of this study is larger, and with the extension of followup time, the analysis and comparison found that the mOS of the two groups of patients with different mutation sites also has significant differences.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Compared with 19DEL, L858R lung cancer patients have a weaker response to TKI treatment, a worse prognosis, and less survival benefit (mPFS: 9.0 vs. 7.0 months, mOS: 25 vs. 16 months) (41,42). Relevant studies suggest that patients with exon 21 deletion mutations benefit more when treated with TCM combined with EGFR-TKIs, and mPFS is prolonged by 5 months (14). However, the sample size of this study is larger, and with the extension of followup time, the analysis and comparison found that the mOS of the two groups of patients with different mutation sites also has significant differences.…”
Section: Discussionmentioning
confidence: 63%
“…In China, the number of deaths due to cancer in 2014 was as high as 2.296 million, of which lung cancer accounted for 27.3% (13). Surgical radical treatment is still the first choice for lung cancer, but due to atypical early symptoms, about 70% of patients are diagnosed in the late stage, and the 5-years survival rate tends to be <10% (14). Adjuvant chemotherapy is recommended as a traditional first-line treatment; although its curative effect is objective, it has entered a bottleneck period.…”
Section: Discussionmentioning
confidence: 99%
“…Natural products are a major resource for the development of novel drug leads ( Cragg and Newman, 2013 ). Chinese medicine has been extensively documented over the centuries, which has a long history of use in cancer treatment, showing significantly improved therapeutic efficacy, reduced side effects of chemotherapy and prolonged survival ( He et al , 2016a ; Zheng et al , 2017 ). Therefore, the identification of bioactive compounds from Chinese medicine plays a crucial role in the development of new anticancer reagents.…”
mentioning
confidence: 99%
“…Previous report has exhibited the low efficiency of molecular targeted therapy (e.g., tyrosine kinase inhibitors) (20). The efficacy of other treatment methods such as radioactive seed implantation between tumor tissues and traditional Chinese herb in the treatment of advanced lung cancer remains to be verified (21)(22)(23).…”
Section: Discussionmentioning
confidence: 99%